An Analytical Review of Global Financial Market Dynamics: Risk Management Strategies and Monetary Policy - Pramukty, Rachmat; Machdar, Nera Marinda; Istianingsih, Istianingsih; Suroso, Sugeng (Dinasti International Journal of Digital Business Management, 2024)
This study provides an in-depth analytical review of global financial market dynamics with a focus on risk management strategies and monetary policy. Through a thorough analysis of recent developments in financial markets, this study aims to understand the impact of economic, political, and technological factors on financial stability globally.  The research pays particular attention to the risk management strategies employed by market participants, be they companies, investors, or financial institutions. Using an analytical framework, this research identifies various methods and instruments used in managing financial risks, including portfolio diversification, hedging, and derivative financial instruments. In addition, the research also analyzes the monetary policies implemented by central banks in different countries. The focus is on central bank responses to changes in economic and financial conditions and their impact on interest rates, inflation and economic growth. This analysis provides insight into how monetary policy can affect the stability of global financial markets. The results of this study are expected to provide a deeper understanding of the complex dynamics of global financial markets, assist market participants and policymakers in making more informed decisions, and provide a basis for the development of effective risk management strategies amid global economic uncertainty.